SYSTOLIC INTER-ARM BLOOD PRESSURE DIFFERENCE AND COGNITIVE DECLINE: FINDINGS FROM THE INTERPRESS-IPD COLLABORATION. (April 2021) - Clark, Christopher; Boddy, Kate; Warren, Fiona; Mcdonagh, Sinead; Moore, Sarah; Aboyans, Victor; Cloutier, Lyne; McManus, Richard; Shore, Angela; Taylor, Rod; Campbell, John
Abstract : Objective: Hypertension and dementia are associated with older age and each other. As the populations age, prevalence of dementia will rise, representing substantial costs and care burdens for society. Currently, no interventions halt established cognitive decline, therefore approaches focus on prevention. Systolic inter-arm differences (IAD) in blood pressure (BP) and cognitive decline are associated with cardiovascular disease. We recently published initial evidence for associations of IAD with prospective cognitive decline and now present findings from the INTERPRESS-IPD Collaboration, examining associations of IAD with mild cognitive impairment (MCI) development and dementia. Design and method: Individual participant data meta-analyses. We examined time-to-event data for new diagnoses of MCI and dementia, according to IAD status in univariable and multivariable regression models, stratified by study. Multivariable analyses were adjusted for systolic BP, age, sex and highest educational attainment. We also examined changes in Mental State Examination (MSE) scores, with adjustments as above, plus follow-up duration. Results: Mean age was 66.2 years, 55% were female, 84% were of White ethnicity and mean systolic IAD was 7.0 mmHg. During 10-year follow-up, 5.9% of 4, 635 individuals, from 3 cohorts, had new diagnoses of MCI. In univariable analyses, MCI was associated with systolic IAD >/=5mmHg [Hazard Ratio, 1.34 (95%CI 1.04 to 1.72); p=0.022] and >/= 0mmHg [1.33 (1.03 to 1.73); p = 0.032]. After adjustment, associations with systolic IADs >/ = 5mmHg [1.31 (1.02 to 1.67); p = 0.036] and >/=10mmHg [1.29 (0.99 to 1.68); p = 0.056] remained. There were 95 new diagnoses of dementia during follow-up; no associations were observed between dementia diagnosis and IAD. MSE scores were recorded for 2, 709 participants; 15.5% showed clinically meaningful reductions (>/=5 points) during follow-up. Decreases were associated with IADs >/=5mmHg (p=0.004) and >/=10mmHg (p = 0.006) on univariable analyses. After adjustment, associations with IADs >/=5mmHg remained (p = 0.033); age and educational attainment attenuated the association with IADs >/ = 10mmHg (p = 0.11). Conclusions: We present the first time-to-event analyses of MCI development with IAD and demonstrate that systolic IADs >/ = 5mmHg and >/ = 10mmHg are associated with MCI onset. If confirmed, these findings could inform individualised treatment decisions to minimise risk of future cognitive decline.